Does the personal characteristics of the public offering committee members affect the issuance quality? An empirical study based on gender characteristics - Wei Xu; Wenyun Yao; Mengying You (China Journal of Accounting Studies, 2020)
ABSTRACTThe Public Offering Review Committee plays a significant role in China’s capital market, in which the individual determines whether the company can be listed or not, then affect the issuance quality. Most of the previous research take the ‘social connect’ as committee members’ personal characteristics, This paper tests the relationship between the committee members’ gender characteristics and the quality of the issuance. We found that the participation of female committee members significantly lowers the pass rate of applicant companies, and the accounting performance and market performance of listed companies approved by the female committee members are better than those of the listed companies approved by an all-male Committee. In theory, these findings may contribute to the understanding of the decision-making mechanism of the committee members and the role of women in organizational economic decision-making, and may provide certain policy reference in the reform of the offering system and the elimination of gender discrimination.